Draft Annual Plan 2004-05 (Text) Government of Madhya Pradesh - Planning Commission (Planning Commission, 2004)
The state now has 9 Commissioner divisions, 48 districts, 271 tehsils and 313 community development blocks, including 129 tribal development blocks. In consonance with the 73rd Constitution amendment, Madhya Pradesh is the first state to enact a new Panchayati Raj Act in 1993. Under three tier Panchayati Raj, the state has at present 45 District Panchayats and 55392 villages were established.
Government of Madhya Pradesh, Planning, Economics and Statistics Department